Analysing guests' perceptions of full service, upscale downtown hotels : a multi-attribute approach. - Wong, Kai Yew. (2009)
This research strives to identify the competing products and services as per guests perceptions of a full service, upscale downtown hotel. In addition, a comparative analysis of the perception between the hotel management and guests also helps to address part of the issue pertaining to 'Gap 1' of the Service Quality model as proposed by Parasuraman, Zeithaml and Berry.